Telematic education: a reality in post-basic nursing education - Salomé M Meyer (AOSIS, 2001)
No institution is immune to the impact of technological change. Opsomming Geen instansie is immuun teen tegnologiese veranderinge nie. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.